Tribunal constitucional: uma proposta da Ordem dos Advogados do Brasil na constituinte de 1987/88 - Serotini, André (Universidade Federal de São Carlos, 2014)
The aim of this research is the performance of the Bar Association in Brazil concerning the Constituent Process of 1987/88, which was an important political time at the end of the twentieth century in Brazil. Marked by an ambivalence of vocations, the Brazilian Bar Association managed to move self confidently between corporate and institutional interests. It is by taking advantage of this characteristic and its history, mainly related to conflicts of legal and democratic nature, that we are motivated to immerse into a universe of this sui generis institution, drawing Law and Policy closer in such a way that they seem inseparable. The chosen arena, the Constituent of 1987, brings all the characteristic features of a good political novel , full of alliances and strategies. The topic that we report as ideal is the analysis of questions which involve setting up a Constitutional Court, proposed by the association, which went through procedures in the Subcommittee of the Judicial Power and the Public Prosecutor. One of the main obstacles was the centuries-old tradition of the Supreme Constitutional Court, an organ of the Judicial Power, which would be substituted, if the progressive intent of the Bar Association in Brazil had been successful. Moreover, taking this into account, we attempt to clarify which factors contributed to this frustration, even knowing that approximately 75% (seventy five percent) of the constituents belonging to the Subcommittee were professionally declared as lawyers.
Constitutional Court: A proposal from the Bar Association in Brazil in the Constituent Assembly from 1987/88
Keywords: Constituinte; Ordem dos Advogados do Brasil; Tribunal constitucional; Poder judiciário; Controle de constitucionalidade; Constituent; Bar association in Brazil; Constitutional court; Judicial power; Constitutionality control; CIENCIAS HUMANAS::CIENCIA POLITICA